Compact low-field NMR: Unmasking morphological changes from solvent-induced crystallization in polyethylene. (July 2016) - Teymouri, Yadollah; Adams, Alina; Blümich, Bernhard
Graphical abstract: Highlights: Solvent-induced crystallization is accompanied by structural rearrangements in the soft domain of polyethylene. Solvent-induced crystallization proceeds faster at higher temperature. Short-chain branching can accelerate solvent-induced crystallization. Abstract: It is accepted knowledge that solvents diffuse in the amorphous phase of semi-crystalline polymers. Yet these solvents may trigger swelling that affects segmental chain mobility and gives rise to changes of the polymer. This study explores compact low-field NMR as a fast, simple, and low-cost method of analysis to detect such swelling-induced morphological changes. Here, 1 H NMR relaxation, 1 H wide-line NMR spectroscopy, and DSC were employed to investigate the morphological changes of a commercial-brand low-density polyethylene (LDPE) induced by swelling for different durations in different solvents and at three different temperatures. The analysis of the phase composition and relaxation times T 2eff reveals that solvent-induced crystallization (SINC) is accompanied by structural rearrangements in the soft domain that, in turn, increase the amount of the rigid fraction. The variations in the chain mobility of LDPE samples identified by NMR prove that the SINC proceeds faster at higher swelling temperature. Moreover, the changes in the relaxation time of LDPE samples swollen in different solvents suggest that thermodynamic and kinetic factors govern the SINC process. This agrees well with the variations in the degree of crystallinity evaluated by DSC. The NMR data show that short-chain branching may accelerate the SINC process. This study also proves, that compact low-field NMR is an adequate tool for detecting the morphological changes in polyethylene invoked by solvent-induced crystallization.